The Future of the Finno-Ugric Languages of Russia - Pusztay, János (Przegląd Rusycystyczny, 2018)
The article is an approch to characterize the situation of Finno-Ugric langauges in Russia in 21st century on the basis of statistical, legal and sociolinguistic sources. Globalisation prevails in a more or less closed, originally multi-lingual and multi-cultural society mainly due to political or ideological reasons. This situation can be observed in case of Finno-Ugric peoples in Russia. Because of political conditions one-sided bilingualism is the entrance hall to a new (Russian) monolingualism.